Pendampingan Pembuatan NIB Dalam Pengembangan UMKM Catra Laundry dan Can’s Barbershop - Dara Tyas Utami (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Business legality is very important for business actors in the development and sustainability of a business. Business Identification Number (NIB) is an important identity for MSMEs that can increase product attractiveness and make licensing easier. NIB is very profitable in obtaining capital that can be used to optimize its business so that it can compete in the global market. The government has assisted MSMEs through the OSS system in establishing business legality. However, there are still many business actors who lack knowledge and understanding in making business legal. This service is carried out with the aim of resolving this problem, by providing socialization of understanding and assistance in making business legality through Online Single Submission (OSS).